A complication to be aware of: hyperkalaemia following propranolol therapy for an infant with intestinal haemangiomatozis. (19th May 2014) - Belen, Burcu; Oguz, Aynur; Okur, Arzu; Dalgic, Buket
Abstract : Infantile haemangiomas, benign vascular tumours seen in 4–10% of infants are characterised by their spontaneous remission following a 3–9 month period of dynamic growth. Propranolol has been reported to be used as a successful treatment of severe symptomatic infantile haemangiomas. Hyperkalaemia has not been recognised as a serious effect of propranolol since recently. Here, we would like to portray a 2-year-old male patient with intestinal haemangiomatosis who presented with severe hyperkalaemia and was successfully managed with hydration, loop diuretics, potassium binding granules, inhaler β-2 agonists and insulin. To date, this is the first case of intestinal haemangiomatosis complicated with severe hyperkalaemia. Our case suggested the idea of close monitorisation of potassium levels as well as haemodynamic status at the initialisation of the propranolol treatment.